PERAN GERAKAN PRAMUKA UNTUK MEMBENTUK KARAKTER KEPEDULIAN SOSIAL DAN KEMANDIRIAN (STUDI KASUS DI SDIT UKHWAH DAN MIS AN-NURIYYAH 2 BANJARMASIN) - Erliani, Saadah (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
Character education is a step to address the moral decadence problem of learners. Scout movement formulates characters through scouting activities, especially the character of social awareness and independence. The title of this research is the role of Scout Movement to Form Character of Social awareness and Independence (the case of study  was conducted at SDIT Ukhwah and MIS An-Nuriyyah 2 Banjarmasin). The focus of this research is to know how the concepts, the activities and the efforts and roles of the Scout Movement done to form the character of social awareness and independence on the students of SDIT Ukhuwah and MIS An-Nuriyyah 2 Banjarmasin. The purposes to be achieved in this research is how the concepts,  the activities and the role of the Scout movement to form the character of social awareness and independence. This research uses qualitative research approach, and the type is case study research type. Researcher wants to understand the role of scout movement to form the character of students (Case study on students of grade V SDIT Ukhuwah and MIS An-Nuriyyah 2 Banjarmasin).